If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 2x + -12 = 3x + 5 + -1x + 6 Reorder the terms: -12 + 9x + 2x = 3x + 5 + -1x + 6 Combine like terms: 9x + 2x = 11x -12 + 11x = 3x + 5 + -1x + 6 Reorder the terms: -12 + 11x = 5 + 6 + 3x + -1x Combine like terms: 5 + 6 = 11 -12 + 11x = 11 + 3x + -1x Combine like terms: 3x + -1x = 2x -12 + 11x = 11 + 2x Solving -12 + 11x = 11 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -12 + 11x + -2x = 11 + 2x + -2x Combine like terms: 11x + -2x = 9x -12 + 9x = 11 + 2x + -2x Combine like terms: 2x + -2x = 0 -12 + 9x = 11 + 0 -12 + 9x = 11 Add '12' to each side of the equation. -12 + 12 + 9x = 11 + 12 Combine like terms: -12 + 12 = 0 0 + 9x = 11 + 12 9x = 11 + 12 Combine like terms: 11 + 12 = 23 9x = 23 Divide each side by '9'. x = 2.555555556 Simplifying x = 2.555555556
| t^2-7t-44=0 | | -5(v+2)+3v+6=5v+6 | | 0.04x+13=0.4x-8.6 | | 4+5t=54 | | 80x^2-24x^3=0 | | 7(w-4)+4=2(w+11) | | 5x-16=x+1 | | 3x-90+x+38= | | 2(1-2z)-3(2z+9)=z-29 | | 3x+9-6+4x=2x-9+4+3+10x | | 72=-8(-4+4r)-2(1+5r) | | 4x^3+16x^2+2x=0 | | 7(6-2(-37))=5(-3(-37)+1) | | 12n-30=-21+9n+2n | | 2(6x+6x+36)=36x | | 7+8p+8p=-8(1-3p)-7(p-1) | | 14m-10=3(4+1m) | | 4x^3+8x^2+2x=0 | | -3(x+1)+19x-9= | | 6=1/5w+7/5w-4 | | m-3m=-14-4m | | x^3=61.81 | | 1.5n-.5=n+3.25 | | -4(2x-2)=-(4x-4) | | Y^3+y^2-16y+16=0 | | -38=4(7+3p)+5(-2-p) | | -6-4x=26 | | 6k-5k+8k-4k= | | -x^3-6=-7 | | 2(5-2z)-2(4z+6)=z-8 | | -2(7k+4)+9=32 | | (-8)x(6)= |